FIELD PROPERTIES AND SETTLEMENT CALCULATION OF SOIL-CEMENT COLUMN IMPROVED SOFT SUBSOIL - A CASE STUDY - J. C. Chai; S. Y. Liu; Y. J. Du (International Association of Lowland Technology, 2002)
The unconfined compression strength, standard penetration test (SPT) results for soil-cement columns and the field loading tests results of the composite subsoil at Lian-Yun-Gang section, Xu - Lian expressway, China, were presented. The Methods for calculating the settlement of the soil-cement column improved soft subsoil were discussed. It is recommended that the stiffness of the